The Effectiveness of Gender Based Class Segregation in Preventing Dating Behavior in Junior High Schools - Salsabila Tajrin; Budi Haryanto (IQRO: Journal of Islamic Education, 2026)
Dating behavior among junior high school students has the potential to impact student focus and character development. As a preventative measure, Islamic educational institutions implement a gender segregation policy by separating classes between boys and girls. This study aims to describe student dating behavior and explore the effectiveness of gender segregation in preventing such behavior at "Semut Hitam" Junior High School. This study used a descriptive qualitative approach using observation, interviews, and documentation techniques. Informants were selected purposively, including guidance and counseling teachers, student affairs officials, and the school environment. Data analysis was conducted using the Miles, Huberman, and Saldana model. The results indicate that the student segregation policy successfully reduced the frequency of dating behavior. Class separation proved quite effective in limiting direct cross-gender interaction during learning and school activities, supported by teacher supervision, discipline, and the instillation of Islamic values. The effectiveness of this policy is also reflected in some alumni who continue to maintain boundaries with the opposite sex after graduation. Furthermore, peer solidarity was found, with students tending not to disclose hidden dating behavior and leaving the monitoring process to the school's mechanisms.